A Study of the Relationship Between Teachers’ Perception Towards Administrative Support and Their Decision-Making Styles in a Public Middle School, Guizhou Province, China - Yue, Anna; Vinitwatanakhun, Watana (Scholar: Human Sciences, 2021)
This study investigated the relationship between teachers’ perception towards administrative support and their decision-making styles in a public middle school, Guizhou Province, China. This study aimed (1) to identify the level of teachers’ perception towards administrative support; (2) to identify level of teachers’ perception of decision-making styles; (3) To determine the relationship between teachers’ perception towards administrative support and their decision-making styles in a public middle school in Guiyang, Guizhou province, China. The study had 81 respondents, all full-time teachers in the selected middle school and 100% of them responded to the survey. This research used Means and Standard Deviation to analyze the teachers’ perceptions toward the level of administrative support and their decision-making styles. Pearson Product Moment Coefficient of Correlation was used to test the relationship between the two variables. This study found that the teachers had a relatively positive attitude towards administrative support, the perception level in which teachers use decision-making styles was high, and there was a positive relationship between teachers’ perception toward administrative support and their decision-making styles.